2012
DOI: 10.1186/1471-2180-12-262
|View full text |Cite
|
Sign up to set email alerts
|

PHB granules are attached to the nucleoid via PhaM in Ralstonia eutropha

Abstract: BackgroundPoly(3-hydroxybutyrate) (PHB) granules are important storage compounds of carbon and energy in many prokaryotes which allow survival of the cells in the absence of suitable carbon sources. Formation and subcellular localization of PHB granules was previously assumed to occur randomly in the cytoplasm of PHB accumulating bacteria. However, contradictionary results on subcellular localization of PHB granules in Ralstonia eutropha were published, recently.ResultsHere, we provide evidence by transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
69
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 43 publications
(52 reference statements)
7
69
0
4
Order By: Relevance
“…However, the effect of PhaM on PhaC1 activity was not described either by Cho et al or by us. Later, we found by bimolecular fluorescence complementation that PhaM interacts with PhaC1 in vivo in R. eutropha and is responsible for attachment of PHB granules to the bacterial nucleoid (27,29). In the present study, we were able to discover a new (additional) function of PhaM: as little as ϳ16 nM PhaM was sufficient to switch ϳ165 nM PhaC1 from the inactive (lag phase) to the active (no lag phase) form.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, the effect of PhaM on PhaC1 activity was not described either by Cho et al or by us. Later, we found by bimolecular fluorescence complementation that PhaM interacts with PhaC1 in vivo in R. eutropha and is responsible for attachment of PHB granules to the bacterial nucleoid (27,29). In the present study, we were able to discover a new (additional) function of PhaM: as little as ϳ16 nM PhaM was sufficient to switch ϳ165 nM PhaC1 from the inactive (lag phase) to the active (no lag phase) form.…”
Section: Discussionsupporting
confidence: 53%
“…Nucleoid occlusion of PHB granules (50) in growing cells might be one explanation for the frequent observation of periphery-localized PHB granules, and this assumption would allow to keep the micelle model. However, the identification of PhaM as a novel PHB-and DNA-bound protein (27,29) and the in vivo interaction of PhaC1 and PhaM in R. eutropha (43) is in disagreement with the assumption of a random localization of PhaC1 in the cytoplasm. It is more compatible with a third model, the scaffold model, in which the PHB synthase PhaC1 is attached to an internal cellular structure, most likely to the bacterial nucleoid.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently, a Brazilian group determined the proteins of PHB granules isolated from Herbaspirillum seropedicae (30). Remarkably, a histone-like protein with some features similar to those of PhaM and PhaF (11,(22)(23)(24), two outer membrane proteins (OMPs), several hypothetical proteins, and also a protein of the tricarboxylic acid (TCA) cycle (aconitase) were identified, in addition to proteins with well-established functions in PHB metabolism (PHB synthase, the phasin PhaP, and the PHB depolymerase PhaZ). Proteins with functions not obviously related to PHB metabolism had already been identified in earlier studies of PHAaccumulating bacteria.…”
mentioning
confidence: 99%
“…Moreover, at least two proteins were identified that can bind both to the PHB granule and to DNA. One is PhaR, a transcriptional regulator that can be titrated from its DNA binding site by binding to the PHB granule surface (19)(20)(21); the other is PhaM, which is responsible for anchoring PHB granules to the bacterial nucleoid via binding to the PHB synthase PhaC1 and to DNA (11,22,23). A comparable set of PHA granule-associated proteins (PGAPs) is present in the surface layer of medium-chain-length PHA in bacteria such as Pseudomonas putida (reference 24 and references therein) and in all PHA-accumulating species that have been examined, including Archaea (25,26).…”
mentioning
confidence: 99%